The effect of salinity and temperature on the uptake of cadmium and zinc by the common blue mussel, Mytilus edulis with some notes on their survival - Ali, M.; Taylor, A. (Mesopotamian Journal of Marine Sciences, 2022)
This study has investigated the effect of salinity and temperature on the rates of uptake of Cd and Zn by the blue mussel Mytilus edulis under laboratory conditions. Exposure of mussels to concentrations of 2 ppm resulted in an almost linear increase in the concentration of Cd and Zn throughout 14 days of exposure. Only the whole soft tissue of each mussel was frozen, freeze-dried and acid-digested before measuring the level of contamination by the spectrophotometer. Zn uptake was interrupted by elimination periods at high salinity. The uptake of Cd by M. edulis was at its maximum at low salinity and high temperature while at high salinity, temperature did not significantly affect the rate of uptake. Salinity had a significant effect on Zn uptake with the rate of uptake being higher at low salinity. Mortalities of mussels exposed to Cd and Zn along with controls were only observed at low salinity.